A method for enhancing laser damage threshold by gamma-ray irradiation enhanced chemical film

The chemical film samples are treated by gamma ray irradiation, and the irradiation dose is adjusted to improve the mechanical properties of the chemical film and the anti-laser damage performance. This solves the problem that the existing chemical urgency membrane is susceptible to laser damage in high-power laser devices, and achieves a significant improvement in the anti-laser damage ability of the chemical film.

CN115933016BActive Publication Date: 2025-04-25YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211538077.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-02
Publication Date
2025-04-25
Estimated Expiration
2042-12-02

AI Technical Summary

Technical Problem

The existing chemical amplicon membranes are susceptible to laser damage in high-power laser devices, resulting in poor mechanical properties and cannot meet the requirements of inertial constrained fusion devices against laser damage.

Method used

The chemical film sample is treated by gamma ray irradiation and its irradiation dose is adjusted to improve the mechanical properties of the chemical film and its anti-laser damage performance. Specific steps include sample fixation, gamma ray irradiation at different doses, measuring hardness and laser damage threshold, fitting curves to determine the optimal irradiation dose, and performing gamma irradiation hardening treatment.

Benefits of technology

It significantly improves the mechanical properties of the chemical film and anti-laser damage performance, extends the service life of the optical components, and improves the load capacity of high-power laser devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115933016B_ABST
    Figure CN115933016B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for enhancing the laser damage threshold of a chemical film by gamma ray irradiation. Aiming at the problem of poor mechanical properties of the chemical film and the limitations of the prior art, the technical solution of the present invention is: firstly, the chemical film sample is irradiated with different doses of gamma rays; then, the hardness and laser damage threshold of the chemical film under different doses of irradiation are measured, thereby obtaining an irradiation dose-hardness relationship curve and an irradiation dose-laser damage threshold relationship curve to determine the optimal dose required for the irradiation of the chemical film; finally, the chemical film of the same process is subjected to gamma ray irradiation hardening treatment using the optimal irradiation dose. The method of the present invention can significantly improve the mechanical properties and anti-laser damage performance of the chemical film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of material surface modification, and in particular relates to a method for enhancing the laser damage threshold of a chemical film by gamma ray irradiation. Background technology:

[0002] Inertial confinement fusion (ICF) is one of the ways to achieve clean, safe, efficient and sustainable energy. It uses strong lasers to heat nuclear fuel to produce high-temperature and high-pressure plasma to achieve nuclear fusion reactions and release energy, which has attracted widespread attention from countries around the world. High-power solid-state laser devices, such as the National Ignition Facility (NIF) of the United States, the Laser Megajoule (LMJ) of France and the Shenguang III device (SG-III) of China, contain a large number of optical components, such as gratings, windows, shielding plates, lenses, amplifiers, polarizers, and frequency conversion crystals, which are used to control the laser beam to obtain high-energy lasers, thereby initiating fusion reactions. However, the reflectivity of these optical components is as high as ~8%. After the laser passes through thousands of optical components on the optical path, the total laser energy transmitted to the target chamber will be seriously reduced. In order to reduce the reflection loss during the transmission process, the optical components need to be coated with an anti-reflection film on their surface to increase the energy transmission efficiency of the laser. Compared with physical anti-reflection films, chemical anti-reflection films have simple preparation processes, low costs, and are easy to achieve large-scale preparation and mass production. More importantly, the chemical anti-reflection film is made of nanoparticles, and its unique loose structure is conducive to the relaxation of high-energy laser energy, making it have excellent resistance to laser damage. Therefore, chemical anti-reflection films deposited on the surface of optical components are widely used in high-power laser devices.

[0003] In high-power laser devices, chemical anti-reflection films are damaged and fall off after multiple laser irradiations, which seriously affects the anti-laser damage performance of optical components and the load capacity of laser devices, and has become one of the important bottlenecks restricting the development of inertial confinement fusion. Laser damage to chemical films is closely related to intrinsic defects of materials and environmental pollution (such as organic molecular pollution). So far, in order to improve the anti-laser damage performance of chemical films, one is to improve the preparation process of chemical films to reduce their own defects; the other is to improve the stability of chemical films in polluted environments to make them have anti-pollution properties and reduce the adsorption of organic pollutants. Therefore, the absorption of ultraviolet laser energy by chemical films is greatly reduced, which greatly improves its laser damage threshold, but it is still lower than the laser damage threshold of optical components. So far, few people have improved the anti-laser damage performance of chemical films from a mechanical point of view. Chemical films have a loose structure and weak chemical bonds, which makes their mechanical properties poor, but the relaxation of high-energy laser energy requires the film to have a loose internal structure, which is a contradictory demand. In the process of conducting inertial confinement fusion research, the United States found that the original 1.8MJ laser output energy could not achieve the expected fusion drive target, and it was recommended to increase it to 2.6-3.0MJ, which puts higher requirements on the chemical film's resistance to laser damage. Improving the mechanical properties of the chemical film can make it less likely to break under the plasma pressure generated by absorbing the laser. Therefore, preparing a chemical anti-reflection film with excellent resistance to laser damage and high mechanical strength has important economic value and engineering significance for the high-throughput output and stable operation of the laser device.

[0004] At present, in domestic and foreign reports, in order to improve the mechanical properties of chemical anti-reflection films, acid-base catalysis, silane coupling agent cross-linking and thermal annealing are mainly used. Although these methods can improve the mechanical properties of chemical films to a certain extent, the effect is very limited. At present, the existing technology is far from meeting the requirements of significantly improving the mechanical properties of chemical films. Therefore, it is urgent to find a method that can effectively improve the mechanical properties and laser damage resistance of chemical films. Gamma-ray irradiation can promote the migration, aggregation and recombination of internal defects of thin film materials, and at the same time is conducive to the further reaction of chemical groups, thereby significantly improving the mechanical properties and laser damage resistance of chemical films. However, the irradiation dose has an important influence on the above-mentioned properties of chemical films. If the irradiation dose is too large, it may also cause the chemical bonds of the chemical film to break, form various structural defects, enhance the absorption of ultraviolet lasers, and reduce its laser damage threshold. For gamma-ray irradiation of chemical films, the selection of the optimal irradiation dose is particularly important. Due to the diversity of chemical anti-reflection films, it is not easy to determine the optimal irradiation dose. Therefore, the present invention proposes a universal method for enhancing the laser damage threshold of chemical films by gamma-ray irradiation. Summary of the invention:

[0005] In view of the problem of poor mechanical properties of chemical films and the limitations of the prior art, the present invention provides a method for enhancing the laser damage threshold of chemical films by gamma-ray irradiation, which can significantly improve the mechanical properties and laser damage resistance of chemical films.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for enhancing the laser damage threshold of a chemical film by gamma ray irradiation, comprising the following steps:

[0007] (1) For chemical film samples, they were assembled into clean quartz tubes, fixed and melt-sealed. 60 The Co gamma radiation source irradiates the packaged samples with different doses of gamma rays, the irradiation dose is 10 to 1000 kGy, the irradiation dose interval is 10 to 500 kGy, and the dose rate is 1 to 10 kGy / h.

[0008] (2) For the chemical film samples irradiated with different doses of gamma rays in (1), the hardness of the chemical film is measured by a nanoindenter. The indentation depth must be less than the thickness of the film. More than 10 positions are randomly selected for each sample for testing, and the average value is taken as the final hardness of the chemical film under the irradiation dose. Based on the hardness of the chemical film under different doses, the irradiation dose-hardness value relationship curve of the chemical film sample is established.

[0009] (3) For the chemical film samples irradiated with different doses of gamma rays in (1), the laser damage threshold of the chemical film was tested by a laser with a laser wavelength of 355 nm and a pulse width of 6.3 ns. More than 20 positions were randomly selected for testing for each sample, and the average value was taken as the final result of the chemical film under the irradiation dose. Based on the laser damage threshold of the chemical film under different doses, the irradiation dose-laser damage threshold relationship curve of the chemical film sample was established.

[0010] (4) The irradiation dose-hardness relationship curve and the irradiation dose-laser damage threshold curve obtained in (2) and (3) are fitted. In the fitting curve, the irradiation dose corresponding to the maximum value of the hardness and laser damage threshold is the optimal irradiation dose required for the chemical film.

[0011] (5) For the chemical film with the same process as in (1), it is placed in a clean quartz tube, and the sample is fixed and melt-sealed. Based on the optimal irradiation dose obtained in (4), 60 The Co gamma radiation source performs gamma ray irradiation hardening treatment on the packaged chemical film of the same process, thereby obtaining a chemical film with significantly improved mechanical properties and anti-laser damage performance. Steps (1) to (5) are applicable to chemical films prepared by different processes, chemical films of different thicknesses, chemical films of different materials, and substrates of different materials, and also include single-layer films, multi-layer films, and composite films.

[0012] The beneficial effects of the present invention are:

[0013] Gamma-ray irradiation can promote the migration, aggregation and recombination of internal defects in thin film materials, and at the same time is beneficial to the further reaction of chemical groups, thereby significantly improving the mechanical properties and resistance to laser damage of chemical films, which is beneficial to extending the service life of optical components and improving the load capacity of high-power laser devices.

[0014] The present invention can uniformly improve the mechanical properties and laser damage resistance of chemical films of different calibers. The film preparation process, film thickness, film material and substrate type are not limited. The invention is also applicable to single-layer films, multi-layer films and composite films. Description of the drawings:

[0015] Figure 1 It is a schematic diagram of the process of the present invention;

[0016] Figure 2 This is a radiation dose-hardness relationship curve in an embodiment of the present invention;

[0017] Figure 3 is a relationship curve between irradiation dose and laser damage threshold in an embodiment of the present invention;

[0018] Figure 4 is a load-displacement curve of the film before and after gamma ray irradiation in an embodiment of the present invention;

[0019] Figure 5 are the hardness and elastic modulus of the film before and after gamma ray irradiation in the embodiment of the present invention;

[0020] Figure 6 is the laser damage threshold of the film before and after gamma ray irradiation in the embodiment of the present invention. Specific implementation method:

[0021] Example

[0022] Taking the sol-gel SiO2 chemical film on the surface of a 30mm×30mm×4mm fused quartz substrate as an example, the method of enhancing the laser damage threshold of a gamma-ray irradiation-enhanced chemical film of the present invention is further described in detail.

[0023] This example is a sol-gel SiO2 antireflection film with a thickness of 73nm and a fused quartz substrate with a size of 30mm×30mm×4mm. The chemical film samples were divided into 5 groups and placed in a clean quartz tube, and the samples were fixed and melt-sealed. 60The packaged samples were irradiated with gamma rays by a Co gamma radiation source. The irradiation doses were 0 kGy, 10 kGy, 100 kGy, 500 kGy, and 1000 kGy, respectively, and the dose rate was 4.903 kGy / h. The hardness of the chemical film under different irradiation doses was measured by a nanoindenter. The indentation depth was 50 nm. Ten positions were randomly selected for each sample for testing, and the average value was taken as the final hardness of the chemical film under the irradiation dose. Based on the hardness of the chemical film under different doses, the irradiation dose-hardness value relationship curve of the chemical film sample was established, as shown in Fig. Figure 2 As shown in the figure, the R-on-1 laser damage threshold of the chemical film under different irradiation doses was tested by using Nd:YAG laser. The laser energy was increased at equal intervals (0.5 J / cm 2 ), each laser energy is irradiated twice until the sample is damaged, and then another new position is irradiated in the same way. The laser wavelength is 355nm and the pulse width is 6.3ns. 20 positions of each sample are randomly selected for testing, and the average value is taken as the final result of the chemical film under the irradiation dose. Based on the laser damage threshold of the chemical film under different doses, the irradiation dose-laser damage threshold relationship curve of the chemical film sample is established, as shown in Figure 3 As shown; the irradiation dose-hardness relationship curve and the irradiation dose-laser damage threshold curve of the chemical film are fitted. In the fitting curve, the irradiation dose corresponding to the maximum values ​​of the hardness and laser damage threshold is the optimal irradiation dose required for the chemical film, thereby determining that the optimal irradiation dose of the sol-gel SiO2 chemical film is 240kGy.

[0024] Finally, the chemical film of the same process is placed in a clean quartz tube, and the sample is fixed and melt-sealed. 60 The packaged chemical film of the same process was subjected to gamma ray irradiation hardening treatment by Co gamma radiation source, with an irradiation dose of 240 kGy and a dose rate of 4.903 kGy / h. The load-displacement curve, hardness and elastic modulus before and after the optimal dose irradiation were measured by nanoindentation instrument, such as Figure 4 and 5As shown in the figure, the load-displacement curve shows that the film needs a greater load force after gamma ray irradiation for the same indentation depth. Therefore, gamma ray irradiation causes compressive stress in the film, which inhibits the plastic deformation of the indentation. The elastic recovery ratio of the film before irradiation is 67.14%, while the elastic recovery ratio of the film after irradiation increases to 76.30%. The unloading process is a purely elastic process. The compressive stress formed in the material will promote elastic recovery, resulting in a smaller residual depth. The hardness and elastic modulus of the film increased significantly after gamma irradiation. The hardness increased from 0.81GPa to 2.36GPa, an increase of 191.36%, and the elastic modulus increased from 8.869GPa to 21.858GPa, an increase of 146.45%. After gamma irradiation, the film forms compressive stress, which is equivalent to pre-stress field, offsetting or reducing the thermal stress field generated by laser irradiation. In addition, the increase in the mechanical strength of the film makes it less likely to break under the plasma pressure generated by absorbing the laser, thereby reducing the probability of occurrence and growth of laser damage to the chemical film. The R-on-1 laser damage thresholds before and after gamma ray irradiation were tested using a 355nm Nd:YAG laser and were 24.71J / cm 2 and 29.61 J / cm 2 The above results show that the mechanical properties and laser damage resistance of chemical films can be significantly improved by irradiating chemical films with the optimal dose of gamma rays.

[0025] The above descriptions are only preferred embodiments of the present invention, and all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A method for enhancing the laser damage threshold of a chemical film by gamma ray irradiation, characterized in that: The following steps are included: S1. Assemble the chemical film samples into a clean quartz tube, fix the samples and melt-seal them. 60 The packaged samples were irradiated with different doses of gamma rays by a Co gamma radiation source; S2. For the chemical film samples irradiated with different doses of gamma rays in step S1, the hardness of the chemical film is measured by a nanoindenter. The indentation depth must be less than the thickness of the film. More than 10 positions are randomly selected for testing for each sample. The average value is taken as the final hardness of the chemical film under the irradiation dose. Based on the hardness of the chemical film under different doses, a irradiation dose-hardness value relationship curve of the chemical film sample is established; S3, for the chemical film samples irradiated with different doses of gamma rays in step S1, a laser is used to test the laser damage threshold of the chemical film, the laser wavelength is 355nm, the pulse width is 6.3ns, more than 20 positions of each sample are randomly selected for testing, and the average value is taken as the final result of the chemical film under the irradiation dose, and based on the laser damage threshold of the chemical film under different doses, an irradiation dose-laser damage threshold relationship curve of the chemical film sample is established; S4, fitting the irradiation dose-hardness relationship curve and the irradiation dose-laser damage threshold curve obtained in steps S2 and S3, wherein the irradiation dose corresponding to the maximum values ​​of the hardness and the laser damage threshold in the fitting curve is the optimal irradiation dose required for the chemical film; S5, based on the optimal irradiation dose obtained in step S4, using 60 The Co gamma radiation source performs gamma ray irradiation hardening treatment on the chemical film of the same process packaged in step S1, so as to obtain a chemical film with significantly improved mechanical properties and anti-laser damage performance.

2. The method for enhancing the laser damage threshold of a chemical film by gamma ray irradiation according to claim 1, characterized in that: Steps S1 to S5 are applicable to chemical films prepared by different processes, chemical films of different thicknesses, chemical films of different materials, and substrates of different materials, and also include single-layer films, multi-layer films, and composite films.

3. The method for enhancing the laser damage threshold of a chemical film by gamma ray irradiation according to claim 1, characterized in that: The irradiation dose of step S1 is 10 to 1000 kGy, the irradiation dose interval is 10 to 500 kGy, and the dose rate is 1 to 10 kGy / h.

Citation Information

Patent Citations

  • Mechanical performance testing method for irradiation material

    CN108827773A

  • Method for greatly improving surface hardness of zirconium-based amorphous alloy through laser irradiation

    CN113278911A